The social distribution of provisioning forest ecosystem services: Evidence and insights from Odisha, India - Lakerveld, R.P.; Lele, S.; Crane, Todd A.; Fortuin, K.P.J.; Springate-Baginski, O. (Elsevier, 2015)
Ecosystem services research has highlighted the importance of ecosystems for human well-being. Most of the research, however, focuses only on aggregate human well-being and disregards distributional and equity issues associated with ecosystem services. We review approaches from institutional economics, political ecology and the social sciences in order to develop an analytical framework to understand the distribution of benefits from ecosystems across different socio-cultural groups and the underlying social processes involved. We then present a case study of the distribution of provisioning ecosystem services in a forest-fringe village in Odisha, India. Our analysis shows the unequal distribution of ecosystem services and complex social processes that determine these. We identify the determining factors and processes to include: differential resource-specific needs, different cultural identities, differentiated social status and bargaining power, exclusionary and inclusionary social practices, differential access. Our analysis proves therefore that aggregation of forest ecosystem benefits obscures crucially important patterns of distribution, and the underlying social processes that determine these. This also demonstrates the necessity of applying social science frameworks in such analyses. Our study also shows that most ecosystem services are co-produced through both ecosystem processes and social actions, and so their assessment cannot be separated from the social context in which they are embedded. In conclusion we recommend that ecosystem services research engages more with process-oriented, context-specific and integrated approaches, based on a recognition of the complexity of social-ecological realities.